PORTABLE HOUSE: ARSITEKTUR BAGI KAUM MISKIN KOTA - Barliana, M Syaom (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2020)
Abstract: One of urban demography problem is the explosion of urban population due to the activity of migration and poverty, including structural poverty. One of the urban poos groups is the scavengers. This paper, have no intention at all to discuss regarding poverty problem, including scavengers from the perspective of economic solution, rather, will study from the perspective of experimental architecture. Mayeng scavengers become the object of case study, because rare for architecture to discuss about this lower class society. The assumption is architecture shoud play a role in the context of social, due to its intervention will influence and further change the face and features of the city. In relation to that, this paper have a purpose to analyse the need of housing for scavengers, also obtained solution of design optimally, even in the context of experimental architecture. Â Keywords: poor society, structural poverty, mayeng scavenger, portable houseAbstrak: Salahsatu problema demografi perkotaan, adalah ledakan populasi penduduk akibat migrasi dan kemiskinan, termasuk kemiskinan struktural. Salahsatu kelompok miskin kota adalah para pemulung. Paper ini, sama sekali tidak bermaksud untuk membahas problematika kemiskinan, termasuk pemulung dari sudut pandang solusi ekonomi, akan mengkaji dari sudut pandang arsitektur eksperimental. Pemulung mayeng menjadi objek studi kasus, karena arsitektur sangat jarang menyentuh masyarakat kelas bawah ini. Asumsinya, arsitektur harus memainkan peran dalam konteks social, karena intervensi arsitektur akan mempengaruhi dan bahkan mengubah perjalanan wajah dan fitur kota. Sekaitan itu, paper ini bertujuan untuk menganalisis kebutuhan tempat tinggal bagi pemulung, serta menemukan solusi desain secara optimal, meskipun berada pada konteks arsitektur eksperimental.Â Kata kunci : masyarakat miskin, kemiskinan struktural, pemulung mayeng,Â portable house